Engendering Technology in the Digital Age: Women’s Agency, Entrepreneurship and Multitasking Whirlpool - Irene Kamberidou ("Politics of Technologies in the Digital Age". Organizers: University of Ioannina (Department of Philosophy), the National and Kapodistrian University of Athens (Department of Sociology), and Ionian University (Department of History)., 2024)
Forthcoming (cite as):  Kamberidou, Irene (2024). Engendering Technology in the Digital Age: Women’s Agency, Entrepreneurship and Multitasking Whirlpool. Presentation at the international conference Politics of Technologies in the Digital Age, Nov. 21-23, 2024. Organizers: University of Ioannina (Department of Philosophy), the National and Kapodistrian University of Athens (Department of Sociology), and Ionian University (Department of History): https://politicsoftechnologies.org/  https://pergamos.lib.uoa.gr/uoa/dl/object/3420001